Association between detectable SARS‐COV‐2 RNA in anal swabs and disease severity in patients with coronavirus disease 2019. Issue 2 (27th July 2020) - Lin, Weiyin; Xie, Zhiwei; Li, Yueping; Li, Liya; Wen, Chunyan; Cao, Yi; Chen, Xiaoting; Ou, Xu; Hu, Fengyu; Li, Feng; Tang, Xiaoping; Cai, Weiping; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA was found in the intestines and feces, but its clinical significance is not completely clear. We aim to characterize the longitudinal test results of SARS‐CoV‐2 RNA in anal swabs and to explore the association with disease severity. Methods: We included laboratory‐confirmed coronavirus disease 2019 (COVID‐19) patients, who were hospitalized in Guangzhou Eighth People's Hospital and excluded those who had not received anal swabs for SARS‐COV‐2 RNA testing. Epidemiological, clinical, and laboratory data were obtained. Throat swabs and anal swabs were collected periodically for SARS‐COV‐2 RNA detection. Results: Two hundred and seventeen eligible patients (median aged 50 years, 50.2% were females) were analyzed. 21.2% (46/217) of the patients were detected with SARS‐CoV‐2 RNA in anal swabs. The duration of viral RNA was longer, but the viral load was lower in anal swabs than throat swabs in the early stage of the disease. During a median follow‐up of 20 days, 30 (13.8%) patients were admitted to the intensive care unit (ICU) for high‐flow nasal cannula or higher‐level oxygen support measures to correct hypoxemia. Detectable viral RNA in anal swabs (adjusted hazard ratio [aHR], 2.50; 95% confidence interval [CI], 1.20‐5.24), increased C‐reactive protein (aHR, 3.14; 95% CI, 1.35‐7.32) and lymphocytopenia (aHR, 3.12; 95% CI, 1.46‐6.67) were independently associated with ICU admission. The cumulative incidence of ICU admission was higher among patients with detectable viral RNA in anal swabs (26.3% vs 10.7%, P = .006). Conclusion: Detectable SARS‐CoV‐2 RNA in the digestive tract was a potential warning indicator of severe disease. Highlights: We longitudinally detected the SARS‐CoV‐2 RNA in anal swabs and throat swabs, and explored the association with disease severity of COVID‐19. 21.2% of COVID‐19 patients were detectable for SARS‐CoV‐2 RNA in annal swabs. The duration of virus was longer, but the viral load was lower in anal swabs than throat swabs. Patients with detectable viral RNA in anal swabs had a 2.5‐fold higher risk of ICU admission (26.3% vs. 10.7%, P = 0.006). Detectable SARS‐CoV‐2 RNA in the digestive tract was a potential warning indicator of severe disease. Screening the virus in digestive tract, close monitoring and early intervention of patients with detectable virus are needed.